(untitled) (Journal of Human Sciences, 2023)
This research is concerned with mentioning the sayings and directives of Imam Malik related to raising children. The research came in an introduction, two topics, and a conclusion. The introduction included the problem of the research, its importance, the research plan, and its methodology. As for the introduction, it introduced Imam Malik and mentioned the linguistic and terminological definition of the concept of education. As for the topic, The first is about the responsibility of raising and educating the child. As for the second requirement, I mentioned the advice and directives of Imam Malik. The research was concluded with a conclusion in which the results of the research were mentioned, which are: Raising and the child raising begins from the time he emerges into this world, and distinguishes the upbringing of Imam Malikfor the child in all aspects of education and that Imam Malik’s upbringing of the child is based on ease, compassion, and severity in its proper place, and not burdening the child with public responsibilities.